2020
DOI: 10.1155/2020/6573153
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Danger Signs: Knowledge, Attitude, Health-Seeking Action, and Associated Factors among Postnatal Mothers in Nekemte Town, Oromia Region, Western Ethiopia—A Community-Based Cross-Sectional Study

Abstract: Background. Maternal mortality remains unacceptably high due to pregnancy complications and remains the major health problems in many developing countries such as Ethiopia. Having poor knowledge of obstetric danger signs contributes to delays in seeking and receiving skilled care which in turn increases maternal mortality. However, in Ethiopia, studies are lacking regarding the knowledge level of mothers about obstetric danger signs during pregnancy, child birth, and postnatal periods. In Ethiopia, the proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
4
11
1
Order By: Relevance
“…This was in line with the findings of a study done by Abdi. [ 24 ] Similar findings were noted by Wassihun et al ,[ 19 ] Regasa et al ,[ 21 ] and Liben et al . [ 25 ] Educated women were more likely to have a better understanding of the information they receive through various media.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This was in line with the findings of a study done by Abdi. [ 24 ] Similar findings were noted by Wassihun et al ,[ 19 ] Regasa et al ,[ 21 ] and Liben et al . [ 25 ] Educated women were more likely to have a better understanding of the information they receive through various media.…”
Section: Discussionsupporting
confidence: 78%
“…[ 20 ] Several other studies had shown to vary the proportion of women having good knowledge about danger signs between 32% and 66%. [ 19 21 22 23 ] This difference in the knowledge of danger signs could be attributed to variation in terms of socio-demographic and geographical characteristics, health services coverage, and difference in the sampling technique.…”
Section: Discussionmentioning
confidence: 99%
“…2 It was noted that almost 80% of maternal deaths occur due to direct obstetric complications including severe haemorrhage, pregnancy-induced hypertension, infections, and obstructed and prolonged labour. 3 According to Nepal Demographic and Health Survey (NDHS) 2016, the maternal mortality ratio (MMR) for Nepal is 239 deaths per 100,000 live births. 4 The Sustainable Development Goals (SDG) also speak the interrelationship of maternal and neonatal health with other aspects of development.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Egypt and Ghana also reported that the vast majority of women consulted a health provider when faced with danger signs or complications [4] [21]. The use of traditional birth attendants was cited by a minority of our participants and by other authors [17].…”
Section: ) Knowledgementioning
confidence: 63%
“…In addition, prolonged labor [15] [17] and intrauterine fetal death [13] are also listed. Further, high frequencies of headache and fever have also been reported by some authors [10] [14] [17] as well as premature rupture of membranes [18].…”
Section: ) Knowledgementioning
confidence: 64%